Science and Technology Studies in Colombia: Research Groups and Collaboration (Información, cultura y sociedad, 2023)
Using bibliometric methods, this work identifies some of the main socio-cognitive characteristics of the academic community of Social Studies of Science and Technology (STS) in Colombia. The analysis, based on information reported in the ScienTI platform run by the Ministry of Science, Technology, and Innovation, focuses on 248 research articles published by the members of ten research groups identified as STS. Pajek, Ucinet and, Vosviewer analysis tools were used to analyze and visualize the collaborative relationships between the groups included in the study. The results suggest that, despite having similar lines of research, there is little collaboration among the STS research groups in Colombia. We identified higher rates of collaboration between STS group members with non-STS identified research academics than between STS group members. The co-authorship network is composed of STS academics and non-STS academics, where those serving as nodes connect with mostly non-STS-academics. When there is a collaboration among STS groups, those belong to the same city. These results offer preliminary elements for the description of this community, but also show the need to broaden the exploration to other types of production, as well as to try to identify groups and researchers who, even without explicitly identifying themselves as dedicated to STS, use the theoretical-methodological repertoires and make contributions to this field.